Penentuan Kelayakan Kandang Sapi Menggunakan Analytic Hierarcy Process-Weighted (AHP-WP) [Studi Kasus UPT Pembibitan Ternak Dan Hijauan Makanan Ternak Singosari] - Firnanda Al Islama Achyunda Putra; Nurul Hidayat; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The cow shed is a place to live a day cow. The better quality and materials of the cow cow will certainly make the cow better for its development. Therefore, it is important that a decent cow shed plays an important role also on cow health. Today many people do not meet the correct criteria for cow breeding. As a result many cows that died suddenly due to less healthy cages. Therefore, the authors chose this topic because according to the interviews UPTD that this application will help local farmers, especially malangraya region and generally to the community at large. AHP or also called Analytic Hierarcy Process is a decision support model developed by Thomas L. Saaty. This decision support model will describe complex multi-factor or multi-criteria problems into a hierarchy. Variables needed in this study are the criteria for the determinants of the feasibility of the cage as many as 5 criteria. WP or also called Weighted Product acts as a ranking against the weighting that has been done by AHP. So get the results of farmers breeding rank from the lowest to highest rank. This study resulted in an accuracy of 77.3%.